If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x-2)=33+3x
We move all terms to the left:
6(x-2)-(33+3x)=0
We add all the numbers together, and all the variables
6(x-2)-(3x+33)=0
We multiply parentheses
6x-(3x+33)-12=0
We get rid of parentheses
6x-3x-33-12=0
We add all the numbers together, and all the variables
3x-45=0
We move all terms containing x to the left, all other terms to the right
3x=45
x=45/3
x=15
| 4(x+1)=6(2x+6) | | 2x−3=-1 | | 4x+6=1+14x | | 2x−3=1 | | 2^(2x)-10*2^x+16=0 | | 15-5x=6-8 | | 9x-11=3x+10 | | 7/x−5=6 | | 3e=78-18 | | 5z-3=-48 | | -9x(x+12)=-27 | | x+10=-3x | | 9b+7=-20 | | 3xX-1=0 | | y/5-2.4=-14.9 | | 9x+24+3x+12=180 | | 9x+24+3x+12=90 | | 2x^2+3x-35=- | | a²-10a+25=0 | | 4x+5=x=41 | | x-6=7x+5 | | .5(5x-1)=3 | | x+6=7x-5 | | 5,1-x=-8x+1,7x | | 5,5x+1,5=9x+6x | | 3b+10=46 | | 11x+3=8x+7x | | 5y=3y+3 | | 11÷4x+9=3 | | x²+4x-96=0 | | 12(12x+4)=144 | | 39=3x-6. |